Artemis Fowl : the Arctic incident - Colfer, Eoin. (New York : Disney/Hyperion Books, 2009)
When Artemis learns that his father has been kidnapped by the Russian mob, he races to the Arctic Circle to make a daring rescue, where he finds an old acquaintance, Captain Holly Short, who is investigating a plot of the goblin mob.
Originally published: New York : Hyperion Books For Children, 2002.
Accelerated Reader/Renaissance Learning
Keywords: Fairies -- Fiction; Magic -- Fiction; Fathers and sons -- Fiction; Organized crime -- Fiction; Fairies -- Juvenile fiction; Kidnapping -- Juvenile fiction; Magic -- Juvenile fiction; Fathers and sons -- Juvenile fiction; England -- Juvenile fiction; Fairies; Fathers and sons; Kidnapping; Magic; England; Fiction; Juvenile works